Допринос процени психолошких ризика у академији коришћењем Карасекових и Сиегристових модела - студија случаја: универзитет Константин I, Алжир - Aouad, Razika; Ramdane, Bouzerara; Rachid, Chaib; Verzea, Ion (Serbian Journal of Management, 2023)
This study is devoted to psychosocial risks in the university environment. Exposure to psychosocial risks is detailed using existing job and professional nomenclatures. Prevention approaches are all the more effective if they are adapted to the field in which they are deployed. After reviewing each dimension, an analysis of overall exposure to PSRs is carried out. The objective of our study is to contribute to the evaluation of psychosocial risks of university administration personnel, by proposing solutions and recommendations. As a case study, we have taken the Faculty of Science and Technology of the University of Constantine1, Algeria. This study is based on the KARASEK model, composed of 26 questions, and then completed with 6 questions of the SIEGRIST model. As a result of the study, most of the employees suffer from work stress and psychological stress. Therefore, the management should implement preventive actions that meet the expectations of the employees to encourage, appreciate and support them at work.
Keywords: КАРАСЕК и СИЕГРИСТ модел; психолошки ризици; напрезање у послу; универзитет